Digital Warfare and Computational Propaganda in the Israeli-Hamas War: An Analysis of the Influence of Perception Warfare on Conflict Dynamics - Polanunu, Halmar Said Abdul Basir (Eduvest - Journal of Universal Studies, 2025)
The prolonged conflict between Israel and Hamas has experienced significant escalation, particularly following the events of October 7, 2023. This escalation has shifted the confrontation from conventional warfare to digital battlegrounds, where both parties engage in cyber and narrative warfare. The increasing use of digital platforms highlights a new dimension of conflict: the battle for public opinion and international legitimacy. This study aims to analyze the role of propaganda warfare within the Israel-Hamas conflict through a qualitative approach and descriptive-analytical method. The research is framed using computational propaganda theory and digital diplomacy concepts, utilizing primary and secondary data sources critically assessed through literature review and digital media observation. The findings reveal that both Israel and Hamas systematically employ digital platforms to frame narratives that justify military actions, influence global opinion, and gain strategic advantage. Propaganda content is carefully curated to evoke international sympathy and mobilize political support. Social media, in particular, emerges as a powerful tool for operationalizing digital warfare tactics, shaping public perception, and sustaining momentum in the global discourse surrounding the conflict. The study concludes that digital propaganda has become a central strategy in modern asymmetric warfare. Its growing influence demands increased digital literacy and critical media analysis, especially in conflict zones. This research contributes to a deeper understanding of how contemporary conflicts evolve in the digital sphere and emphasizes the need for regulatory frameworks to address the misuse of digital platforms in international disputes.